Hubungan Sarapan Pagi di Rumah dan Jumlah Uang Saku Dengan Konsumsi Makanan Jajanan di Sekolah Pada Siswa SD N Sukorejo 02 Semarang - Rohmatun Lil Alamin; Agustin Syamsianah; Mufnaetty - (Universitas Muhammadiyah Semarang, 2014)
School-age children is an investment the nation , one day they will become the successor cadre development in Indonesia. Government should strive to improve the quality of human resources that should be done early , by way of improving quality in terms of both health and intelligence in a systematic and sustainable . School-age children development and learning achievements require adequate nutrient intake , both in terms of quantity and quality. Before leaving for school, children are expected to have breakfast in the morning at home ( Hidayat , 1995: 597 ) . The purpose of this study to know the relationship between breakfast at home and the amount of pocket money with snack consumption at the school. . The research used an explanatory research and approached by cross sectional methode. The method of collecting data used by the interview survey and using questionnaires. The population in this study were all elementary school students at Semarang City but an accessibility population is all students at Sukorejo N 02 elementary school Semarang . The size of population was 254 students. The sample is taken.by purposive sampling technique, for 4’d and 5’d grade at the elementary school.. The results showed that 85.4 % of respondents do breakfast at home , 65.8 % of respondents had pocket money IDR 3,146.00 average , 72.0 % of respondents consume 2 number of types of snack. The chi square test used for data analysis showed that there is a significant relationship between breakfast at home with the snack consumption at school ( p value = 0.007 and . α = 0.05 ). . Based on the research, Spearman rank correlation test used for data analysis showed that there is a relationship between the amount of pocket money to get a snack with the snack consumption at schools . Preferably before go to school, the student doing breakfast at home and they are given education about the importance of eating breakfast, when they are at the school.